O'Reilly software architecture conference 2017, London, UK. (O'Reilly Media, 2017)
"SACON London 2017 was a unique event, covering the full scope of a software architect's job in breadth, depth, and detail. If software architecture plays any part in your business--and in today's world it most likely does--then this video compilation is for you."--Resource description page